An investigation of regional variations in the biaxial mechanical properties and stress relaxation behaviors of porcine atrioventricular heart valve leaflets. (23rd January 2019) - Laurence, Devin; Ross, Colton; Jett, Samuel; Johns, Cortland; Echols, Allyson; Baumwart, Ryan; Towner, Rheal; Liao, Jun; Bajona, Pietro; Wu, Yi; Lee, Chung-Hao
Abstract: The facilitation of proper blood flow through the heart depends on proper function of heart valve components, and alterations to any component can lead to heart disease or failure. Comprehension of these valvular diseases is reliant on thorough characterization of healthy heart valve structures for use in computational models. Previously, computational models have treated these leaflet structures as a structurally and mechanically homogenous material, which may not be an accurate description of leaflet mechanical response. In this study, we aimed to characterize the mechanics of the heart valve leaflet as a structurally heterogenous material. Specifically, porcine mitral valve and tricuspid valve anterior leaflets were sectioned into six regions and biaxial mechanical tests with various loading ratios and stress-relaxation test were performed on each regional tissue sample. Three main findings from this study were summarized as follows: (i) the central regions of the leaflet had a more anisotropic nature than edge regions, (ii) the mitral valve anterior leaflet was more extensible in regions closer to the annulus, and (iii) there was variance in the stress-relaxation behavior among all six regions, with mitral valve leaflet tissue regions exhibiting a greater decay than the tricuspid valve regions. This study presents a novel investigation of the regional variations in the heart valve biomechanics that has not been comprehensively examined. Our results thus allow for a refinement of computational models for more accurately predicting diseased or surgically-intervened condition, where tissue heterogeneity plays an essential role in the heart valve function.